(untitled) - Gnap, Jozef; Poljak, Milos (Doprava a spoje, 2005)
The paper shows the actual problems of public mass passenger transport financing oriented at regional transport. On the basis of elaborated outputs and costs analysis we could say that regional transport provided by bus transport is economically efficient. The sources mostly created by road transport are reallocated without future strategy, mostly taking account to ensure the transport service in the territory of Slovak Republic by public mass passenger transport.